2020
DOI: 10.1103/physrevb.102.174418
|View full text |Cite
|
Sign up to set email alerts
|

Lee-Yang theory, high cumulants, and large-deviation statistics of the magnetization in the Ising model

Abstract: We investigate the Ising model in one, two, and three dimensions using a cumulant method that allows us to determine the Lee-Yang zeros from the magnetization fluctuations in small lattices. By doing so with increasing system size, we are able to determine the convergence point of the Lee-Yang zeros in the thermodynamic limit and thereby predict the occurrence of a phase transition. The cumulant method is attractive from an experimental point of view since it uses fluctuations of measurable quantities, such as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…Having characterized each of the two dynamical phases, we now go on to investigate the transition between them. To this end, we make use of Lee-Yang theory [29][30][31][32][33][34][35] by considering the zeros of the factorial moment generating function [56][57][58][59][60][61][62][63][64][65][66][67], which for our purposes plays the role of the partition function in equilibrium statistical mechanics [39][40][41][42][43][44][45][46][47]. However, in contrast to thermal phase transitions, we are not considering transitions between different equilibrium phases such as spin lattices with a vanishing or a finite average magnetization.…”
Section: Non-equilibrium Phase Transitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having characterized each of the two dynamical phases, we now go on to investigate the transition between them. To this end, we make use of Lee-Yang theory [29][30][31][32][33][34][35] by considering the zeros of the factorial moment generating function [56][57][58][59][60][61][62][63][64][65][66][67], which for our purposes plays the role of the partition function in equilibrium statistical mechanics [39][40][41][42][43][44][45][46][47]. However, in contrast to thermal phase transitions, we are not considering transitions between different equilibrium phases such as spin lattices with a vanishing or a finite average magnetization.…”
Section: Non-equilibrium Phase Transitionmentioning
confidence: 99%
“…Using these properties, we may invert the relation in Eq. ( 37) to find the real and absolute part of the closest conjugate pair of zeros, s 0 and s * 0 [42][43][44][45], 21).…”
Section: A Lee-yang Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The Lee-Yang formalism has in recent years experienced a surge of interest because of several experiments that have determined the partition function zeros in a variety of physical systems [12][13][14][15] and thereby shown that Lee-Yang zeros are not just a theoretical concept. In fact, they provide an efficient tool to predict and understand phase transitions in interacting many-body systems, also experimentally [16][17][18][19][20]. However, while the focus so far has been on classical systems, a Lee-Yang theory to describe quantum phase transitions is now clearly becoming desirable [21].…”
mentioning
confidence: 99%